Implementasi Kurikulum Merdeka Melalui Peran Komunitas Belajar Intrasekolah dalam Mengoptimalkan Pembelajaran Berdiferensiasi di Sekolah Dasar - Andi Susilowati, Wahyureni; Sukartiningsih, Wahyu; Alfi Muhimmah, Hitta (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
This study aims to analyze the implementation of intra-school learning communities in improving the quality of differentiated learning in Elementary Schools. This study uses a qualitative approach with a case study design at Rejomulyo State Elementary School. Data collection techniques in this study were carried out through observation, in-depth interviews, and document analysis. The results of the study indicate that intra-school learning communities play an important role in optimizing differentiated learning through various aspects, namely increasing teacher knowledge and skills, increasing collaboration between teachers, and increasing teacher motivation and leadership. However, there are several challenges in implementing this intra-school learning community, namely time constraints, lack of resources, and lack of support from related parties. This study provides recommendations for elementary schools to implement the implementation of the independent curriculum through the role of intra-school learning communities in optimizing differentiated learning by increasing teacher capacity, developing a culture of collaboration, utilizing science and technology, and evaluating and reflecting to make continuous improvements and developments.